2013
DOI: 10.1088/0963-0252/22/2/025016
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hydroxyl radical (OH) concentration in an argon RF plasma jet by laser-induced fluorescence

Abstract: The concentration of hydroxyl (OH) radicals in a plasma pencil, an atmospheric RF plasma jet ignited in argon, was measured by laser-induced fluorescence calibrated by Rayleigh scattering on ambient air. A suitable excitation scheme for this discharge was suggested based on laser excitation to the lowest vibrational level of the A 2 + state. Effects of spectral overlap between the laser and absorption line, fluorescence saturation, temporal evolution of fluorescence radiation, rotational energy transfer and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Therefore, at low Ar flow rates the active discharge did not reach the measurement point and the OH concentration in the effluent was low. The increase in Ar flow results in a sharp increase in OH concentration.This can be explained as follows[167]. When the RF power delivered to the plasma was 80 W, the visible active discharge reached the measurement point when the flow rate was approximately 0.3 L/min.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, at low Ar flow rates the active discharge did not reach the measurement point and the OH concentration in the effluent was low. The increase in Ar flow results in a sharp increase in OH concentration.This can be explained as follows[167]. When the RF power delivered to the plasma was 80 W, the visible active discharge reached the measurement point when the flow rate was approximately 0.3 L/min.…”
mentioning
confidence: 95%
“…Comparison of Rayleigh based approaches with chemical kinetics modelling show the advantage of using scattering for optical calibration [160,166,167].…”
mentioning
confidence: 99%
“…At atmospheric pressure, RET is sometimes so fast that the excited state is practically all the time in rotational equilibrium [20,34]. In such a case, each vibrational state can be treated as only one effective level, which simplifies the LIF data processing considerably.…”
Section: Collisional Processesmentioning
confidence: 99%
“…N Xi denotes the concentration of OH radicals in the particular rotational level of the ground vibronic state X 2 Π v 00 ¼ 0 ðÞ from which the excitation occurred, B is the absorption coefficient of the particular excitation transition, c is the speed of light and κ is the overlap term of the absorption and laser line [20], E f is the mean energy of laser pulses during the measurement of the fluorescence, τ is the lifetime of the relevant vibronic state, and…”
mentioning
confidence: 99%
“…[9][10][11][12][13] It is a streamerlike propagation that produces reactive species while it propagates in an ambient air. [16][17][18][19][20][21][22][23][24] For instance, although it is known that the discharge polarity affects the shape, length, and emission profile of the plasma jet, 25 few studies have reported its effect on the reactive species production. 14,15 Although many studies have measured reactive species in the plasma jet, a lot of things are still ambiguous about the relation between the plasma bullet propagation and the production of reactive species.…”
Section: Introductionmentioning
confidence: 99%